Antioxidant Enzyme And Biochemical Behaviour Of Chickpea Cv. Bg-256 And Csg-8962 Under Salt Stress Conditions (Applied Biological Research, 2019)
A pot experiment was conducted to study antioxidant enzyme and  biochemical behaviour of two cultivars of chickpea (Cicer arietinum L.) viz.,  BG-256 (salt sensitive) and CSG-8962 (salt tolerant)] under salt-stress conditions. Salt stress was imposed by applying 50, 100 and 150 mM NaCl to plants as per treatment. Untreated plants were maintained as control.  Plant samples were analyzed from 20 DAS upto 60 DAS at 10-days interval.  Plant height and fresh weight decreased with increasing NaCl treatment.  The antioxidant enzymatic activities (superoxide dismutase, peroxidase and  catalase) and reducing sugar content were stimulated by salt stress. Enhancement was more in tolerant than sensitive cultivar. All the fractions  of photosynthetic pigments and carotenoid content in test plant decreased  gradually with increase in salt level. Decrease was more pronounced in  sensitive cultivar.
Keywords: Antioxidant enzymes; biochemical parameters; chickpea; Cicer arietinum; salinity